Effect of a Regional Outbreak of Coronavirus Disease 2019 on Kawasaki Disease in Korea - Jeong SI; Jung HJ (Dove Medical Press, 2022)
Soo In Jeong, Hyun Joo Jung Department of Pediatrics, Ajou University School of Medicine, Suwon, Republic of KoreaCorrespondence: Hyun Joo Jung, Department of Pediatrics, Ajou University School of Medicine, 164 World Cup-ro, Yeongtong-gu, Suwon, 16499, Korea, Tel +81 31 219 5160, Fax +81 31 219 5169, Email free1109@ajou.ac.krPurpose: The association between coronavirus disease 2019 (COVID-19) and Kawasaki disease (KD) remains controversial. Prior to the nationwide epidemic of COVID-19, there was a unique, large-scale, regional outbreak in Daegu and Gyeonsangbuk-do (DG) in Korea in the spring of 2020. We evaluated the impact of COVID-19 on KD by comparing the characteristics of KD incidence between epidemic and non-epidemic regions in Korea.Patients and Methods: We analyzed nationwide Health Insurance Review and Assessment (HIRA) data to estimate KD incidence from February 2019 to July 2020. Patients below 18 years who were admitted with KD and administered both intravenous immunoglobulin and aspirin (ICD-10 code M303 for KD) were included in the study. We compared the incidence of KD in DG and other regions by analyzing the period-specific incidence from February to May before and after the COVID-19 era.Results: A total of 4461 patients were identified to have KD nationwide from February 2019 to July 2020. The nationwide incidence of KD was significantly reduced during this period compared with the period from February 2018 to July 2019 (p < 0.001). In the DG region, within the 0- 4-years age group, there was no significant difference in the incidence of KD between periods (p = 0.714). In the 5- 9 years age group, a significant decrease in KD incidence was observed in the DG region and all other regions from February 2019 to July 2020.Conclusion: There was a significant decrease in nationwide KD incidence during and until 2 months after the local epidemic in Korea. However, no significant decrease in KD incidence was observed in the 0- 4 years age group in the DG region where the local COVID-19 outbreak occurred. A larger study is necessary to determine the correlation between KD in this age group and the COVID-19 outbreak.Keywords: mucocutaneous lymph node syndrome, seasonal incidence, SARS-COV-2, social distancing, Republic of Korea